CoInGP - Jakobovic, Domagoj (2022)
Jakobovic, D., Manzoni, L., Mariot, L., Picek, S., & Castelli, M. (2021). CoInGP: Convolutional inpainting with genetic programming. In GECCO 2021 - Proceedings of the 2021 Genetic and Evolutionary Computation Conference (pp. 795-803). (GECCO 2021 - Proceedings of the 2021 Genetic and Evolutionary Computation Conference). Association for Computing Machinery, Inc. https://doi.org/10.1145/3449639.3459346